UPAYA PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) - Didik Dewanti (UNIVERSITAS SLAMET RIYADI, 2021)
The purpose of this study was to determine the learning motivation of Class XI MIPA 2 Madrasah Aliyah Negeri 2 Sragen using the STAD style cooperative approach in the second semester of 2015/2016 and to determine the learning achievement in the second semester of the year of Class XI MIPA 2 students in Madrasah Aliyah Negeri 2 Sragen. 2015/2016 used the cooperative approach of the STAD sort. Classroom action analysis is used in this category of study. This study was carried out in MIPA 2 MAN 2 Sragen class XI. The students of class XI MIPA 2, with 37 students, are the focus of this classroom action study. Data processing approaches included the method of reporting and the method of checking. The findings revealed that instructor performance, student learning behaviors, learning abilities, student activity and learning outcomes could be improved by the STAD process. The success of teachers improved from cycle I to cycle II in applying the teaching and learning process. In the excellent benefit group of the pre-cycle of 19 learners, the learning attitude of students has increased. In Phase I, the positive value group increased by 33 from pre-cycle to cycle I and cycle II skills acquired by students. Motivation for learning rose to 95.41 percent . Learning scores improved to 68.5. In cycle I, the number of students who completed the pre-cycle rose by 29 students to 26 students, and again to 37 students in cycle II. Keywords: Academic Achievement, STAD, Motivation to Learn ABSTRAK Tujuan penelitian ini adalah untuk mengetahui motivasi belajar siswa kelas XI MIPA 2 Madrasah Aliyah Negeri 2 Sragen dengan menggunakan pendekatan kooperatif gaya STAD semester genap tahun 2015/2016 dan untuk mengetahui prestasi belajar siswa kelas XI MIPA 2 di kelas. Siswa XI MIPA 2 di Madrasah Aliyah Negeri 2 Sragen. 2015/2016 menggunakan pendekatan kooperatif jenis STAD. Analisis tindakan kelas digunakan dalam kategori studi ini. Penelitian ini dilaksanakan di MIPA 2 MAN 2 Sragen kelas XI. Siswa kelas XI MIPA 2 yang berjumlah 37 siswa menjadi fokus pembelajaran tindakan kelas ini. Pendekatan pengolahan data meliputi metode pelaporan dan metode pengecekan. Hasil penelitian menunjukkan bahwa kinerja instruktur, perilaku belajar siswa, kemampuan belajar, aktivitas siswa dan hasil belajar dapat ditingkatkan dengan proses STAD. Keberhasilan guru meningkat dari siklus I ke siklus II dalam menerapkan proses belajar mengajar. Pada kelompok manfaat sangat baik pra siklus 19 peserta didik, sikap belajar peserta didik mengalami peningkatan. Pada tahap I, kelompok nilai positif meningkat 33 dari prasiklus ke siklus I dan keterampilan yang diperoleh siswa pada siklus II. Motivasi belajar naik menjadi 95,41 persen. Skor pembelajaran meningkat menjadi 68,5. Pada siklus I jumlah siswa yang tuntas pada prasiklus meningkat 29 siswa menjadi 26 siswa, dan kembali menjadi 37 siswa pada siklus II. Kata Kunci : Prestasi Belajar, STAD, Motivasi Belajar